Media bias and advertising: Evidence from a German car magazine - Ralf Dewenter; Ulrich Heimeshoff (Helmut-Schmidt-Universität - Universität der Bundeswehr Hamburg, Fächergruppe Volkswirtschaftslehre, 2014)
This paper investigates the existence of a possible media bias by analyzing the impact of automobile manufacturer's advertisements on automobile reviews in a leading German car magazine. By accounting for both endogeneity and sample selection using a two-step procedure, we find a positive impact of advertising volumes on test scores. The main advantage of our study is the measurement of technical characteristics of cars to explain test scores. Due to this kind of measurement, we avoid serious biases in estimating media bias caused by omitted variables.
Keywords: L15; L82; 330; Car magazines; Media bias; Selection model; Instrumental variable estimation